The shadow of fear: hate crime victimization and stress after Charlottesville - Hellyer, Joshua; Gereke, Johanna (Frontiers in Psychology, 2024)
Recent years have witnessed an increase in highly publicized attacks targeting members of ethnoracial and religious minority groups. To date, existing research has primarily focused on the tendency for such "trigger events" to generate violent aftershocks. We argue that beyond such ripple effects, highly salient trigger events significantly increase hate-crime related stress among racial and ethnic minorities. Additionally, we explore whether these effects are limited to the group most clearly targeted, or if they "spill over" to other minoritized communities. To study reactions to hate crimes, we draw upon national survey data in combination with a natural experiment involving the Unite the Right rally and vehicle attack in Charlottesville, Virginia in August 2017.We first show that there was an increase in anti-Black hate crimes in the two weeks following the Charlottesville incident. We also find a corresponding increase in stress due to the perception of personal vulnerability to hate crimes among African-Americans. However, we do not observe a significant increase in levels of stress following the trigger event among Hispanics and Asian Americans, suggesting that both violent aftershocks and the general climate of fear spurred by hate crimes may be racially bounded.